Thermal analysis of marine structural steel EH36 subject to non-spreading cryogenic spills. Part II: finite element analysis - Mokhtari, Mojtaba; Nam, Woongshik; Amdahl, Jørgen (Ships and offshore structures, 2022)
In Part I of this paper, six liquid nitrogen (LN 2 ) pool boiling tests were carried out to locally cool down six different EH36 steel plates to cryogenic temperatures. Leindenfrost and Critical Heat Flux (CHF) points of LN 2 boiling curve were estimated. These estimations together with the recorded temperature histories are used in this part for the development of a heat flux curve for EH36 steel-LN 2 pool boiling through Finite Element Thermal Analysis (FETA) of the problem investigated experimentally in Part I. Thermal conductivity and heat capacity of EH36 are defined by two unprecedented temperature functions based upon experimental studies in cryogenic temperatures. A user subroutine written in FORTRAN defines the air convection coefficient as a function of surface-air temperature difference, which changes with time and location. Results of this study contribute to the Accidental Limit State (ALS) design of marine and offshore structures for liquified gas spill scenarios.